simulasi RFID dari supply chain management menggunakan blockchain - Ahmad Fali Oklilas; Arif Tumpal Leonardo Sianturi; Huda Ubaya; Rossi Passarella; iman saladin b. azhar (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Blockchain is a collection of blocks that are placed in a sequential order and can hold data containing past transactions. The blockchain has various qualities and benefits, including the fact that it is decentralized and immutable. Blockchain is widely employed in different sectors due to its advantages; one example is supply chain management. In this study, supply chain management is performed with two RFID simulation scenarios, where RFID antennas operate as supply chain management nodes grouped in such a manner as to establish a flow of goods delivery trips, and then products travel is carried out with RFID tags as product IDs. This study creates a simulation tool that can include supply chain management data into the blockchain, having transparency, traceability, and data security.Keywords: Blockchain, Supply chain management, RFID, Data Security, Transparency, Traceability, Immutable.